2003
DOI: 10.1016/s0266-7681(03)00221-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tension in the Aetiology of Dupuytren’s Disease; a Prospective Trial

Abstract: Tension in the palmar fascia has been proposed as a factor causing Dupuytren's disease. If tension does stimulate the growth of new Dupuytren's tissue, relieving longitudinal tension should reduce the recurrence rate following surgery. Thirty patients with palmar Dupuytren's contracture of a single ray that affected only the metacarpophalangeal joint were divided into two groups. Both groups had a fasciotomy: one group through a transverse incision that was closed directly and the other through a longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 9 publications
2
40
0
2
Order By: Relevance
“…69 The two non-randomised studies assessing collagenase versus surgery were both conducted in the USA. 71,72 Of the surgery non-randomised studies, one was conducted in several countries, 73 one in the UK, 74 one in Brazil, 57 one in the USA 75 and one in Australia. 76 Nine of the collagenase case series were conducted in the USA 48,77,81,83,[85][86][87][88][89] two in Australia, 78,79 one in the UK, 91 one in Spain, 84 one in several countries, 90 and the remaining one did not report this information.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…69 The two non-randomised studies assessing collagenase versus surgery were both conducted in the USA. 71,72 Of the surgery non-randomised studies, one was conducted in several countries, 73 one in the UK, 74 one in Brazil, 57 one in the USA 75 and one in Australia. 76 Nine of the collagenase case series were conducted in the USA 48,77,81,83,[85][86][87][88][89] two in Australia, 78,79 one in the UK, 91 one in Spain, 84 one in several countries, 90 and the remaining one did not report this information.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…57,[73][74][75][76] The 15 collagenase case series enrolled a total of 3154 participants and analysed 3139 of them. However, some collagenase case series relied on the same patient cohorts 81,87,90 and we could not establish with certainty whether there was duplication of data because of multiple publications.…”
Section: -69mentioning
confidence: 99%
See 2 more Smart Citations
“…Another prospective, pseudo-randomized study of open fasciotomy (not fasciectomy) patients found recurrence in 2 years for 7/14 treated with direct closure and in 2/13 closed with a Z-plasty [14].…”
Section: Dermofasciectomymentioning
confidence: 99%